Особливості використання водопроникних удосконалених покриттів для управління дощовим стоком - Качмар, І. З.; Жук, В. М.; Kachmar, I. Z.; Zhuk, V. M. (Видавництво Львівської політехніки, 2019)
В умовах різкого зростання площ урбанізованих водонепроникних територій питання управління поверхневим стоком є особливо актуальним. Для вирішення цієї проблеми розроблено та досліджено цілу низку методів, що ґрунтуються на накопиченні, тимчасовому затриманні та фільтрації дощового стоку. Використання водопроникних удосконалених покриттів − це ефективний метод регулювання поверхневого стоку, поширений у закордонній практиці, що дає змогу зменшити поверхневий стік, забезпечує його часткове очищення, покращує безпеку руху на дорогах. У роботі проаналізовано ефективність управління дощовим стоком за допомогою водопроникних удосконалених покриттів. Проаналізовано основні конструктивні особливості влаштування систем ВУП для ґрунтів різної проникності. Розглянуто типовий склад пористого бетону та проаналізовано його основні фізико-механічні та гідравлічні характеристики. Окреслено оптимальні діапазони зміни міцності на стиск пористих бетонів (5–30 МПа), об’ємної пористості (15–25 %) та коефіцієнта фільтрації (2–5,4 мм/с), що підтверджено власними експериментальними дослідженнями авторів (коефіцієнт вільної фільтрації − 7,4–23,0 мм/с при об’ємній пористості зразків 0,189−0,349 та міцності на стиск 4,04–13,85 МПа). Проаналізовано можливий вплив холодних кліматичних умов та процесу кольматації на функціонування водопроникних удосконалених покриттів.

In conditions of intensive increasing of urbanized impervious areas, stormwater management became especially relevant. To solve this problem, a number of methods have been developed and investigated, which are based on the retention, detention or filtration of stormwater runoff. Stormwater management by the pervious pavements is an effective method to control surface runoff; it is widely used in foreign practice, allowing to reduce the runoff volume, provides its preliminary treatment, improves the safety on the roads. Efficiency of stormwater management using the permeable pavement systems is discussed in the paper. The review identified four typical pervious paving surfaces: porous concrete, porous asphalt, permeable interlocking concrete pavers, concrete and plastic grid pavers. The main characteristics of these types of pervious pavement are discussed in this paper. Besides the structural features of the previous pavement systems for soils of different permeability are analyzed. The typical composition of porous concrete and its basic physical-mechanical and hydraulic parameters are considered. The optimal ranges of compressive strength of porous concrete (5–30 MPa), volume porosity (15–25 %), and filtration coefficient (2–5.4 mm/s) are determined, which are in good accordance with author’s experimental results (permeability coefficient 7.4–23.0 mm/s, volume porosity 0.189–0.349 and the compressive strength 4.04–13.85 MPa). The possible influences of cold climatic conditions and the clogging process onto the permeable pavements maintenance are discussed. Different methods of maintenance, including vacuum sweeping and high pressure washing are considered.
Features of the use of pervious pavements for the stormwater management
Keywords: управління дощовим стоком; водопроникні удосконалені покриття; пористий бетон; об’ємна пористість; коефіцієнт фільтрації; міцність на стиск; stormwater management; pervious pavement; porous concrete; volume porosity; filtration coefficient; compressive strength; 628.21